Kampen om Kommunedata: Edb-faglighed og organisationskrig mellem HK og PROSA i 1970erne til 1990erne - Andersen, Nina Thrige (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2023)
The Danish labour union HK Kommunal had its 100 year anniversary in may 2023 and one of the big challenges of the union has always been to define and delineate its organizational territory of skills, trades, and professions. as the administrative tasks of the public sector grew still more specialized during the 20th century, HK Kommunal entered into territorial conflitcs with several more recent labour unions who identified themselves more narrowly in terms of skills and functions, and who targeted groups in the labour market that HK Kommunal claimed to already represent. This article investigates the conflict between HK Kommunal and PROSA about who had the ‘right’ to organize It-workers. The focal point is the struggle over collective agreements at the data centers of Kommunedata (owned by the municipalities) from the 1970s to the1990s. HK Kommunal – and the trade union movement belonging to the confederation LO accused PROSA of being a ‘yellow’ union, but as this article will show, that accusation was more organizationally motivated slander than a sober definition. PROSA challenged the norms and territorial logics of the established labour union movement with their tactics and strategies. and while HK Kommunal insisted that It was just another tool in oﬃce-/administrative work – and thus belonged to their organizational territory – PROSA insisted on viewing IT as a profession or skill in its own right and used this as an argument for why IT-workers needed their own union.